PERAN PEMERINTAH DAERAH DALAM MENINGKATKAN KUALITAS PENATAAN DI SEPANJANG IRIGASI PASAR SIPON KECAMATAN CIPONDOH KOTA TANGERANG - Wijaya, Chandra; Gustiana, Rachmat (Jurnal MoZaiK, 2023)
This study aims to analyze the role of local government in improving the quality of the arrangement along Pasar Sipon irrigation in Cipondoh Sub-district. Tangerang City. Irrigation is an important infrastructure in agriculture and irrigation in the area, and a good arrangement is needed to ensure efficient and sustainable use. A qualitative method was used with data collection techniques through interviews, field observations, and document studies. The main respondents in this study were local government officials, farmers, and landowners connected to Pasar Sipon irrigation. The results showed that the local government has an important role in improving the quality of Pasar Sipon irrigation arrangement. In addition, the local government also plays a role in monitoring and regulating the use of irrigation in accordance with the principles of sustainable management. There are obstacles faced by local governments in carrying out their roles, such as budget constraints, lack of trained human resources, and conflicts of interest between stakeholders. Therefore, cooperation between local governments, traders and landowners is needed to achieve better irrigation management. The role of the local government in improving the quality of Pasar Sipon irrigation arrangement is very important to support agriculture and irrigation in Cipondoh Subdistrict, Tangerang City. Local governments need to overcome existing constraints and work together with other stakeholders to achieve sustainable development goals. Keywords: Role, Quality, Structuring